2011
DOI: 10.1002/dvg.20806
|View full text |Cite
|
Sign up to set email alerts
|

Cell plasticity in Caenorhabditis elegans: From induced to natural cell reprogramming

Abstract: Summary: Achieving controlled reprogramming of differentiated cells into a desired cell type would open new opportunities in stem-cell biology and regenerative medicine. Experimentation on cell reprogramming requires a model in which cell conversion can be induced and tracked individually. The tiny nematode, Caenorhabditis elegans, owing to its known cellular lineage, allows the study of direct cell type conversion with a single-cell resolution. Indeed, recent advances have shown that despite its invariant cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 82 publications
1
10
0
Order By: Relevance
“…A number of studies have shown how strikingly easily a differentiated cell can be experimentally reprogrammed not only into an embryonic stem cell-like state (1) but also into another, different, differentiated identity (2). Remarkably, this process, called direct cell-type conversion or transdifferentiation, also occurs naturally (2).…”
mentioning
confidence: 99%
“…A number of studies have shown how strikingly easily a differentiated cell can be experimentally reprogrammed not only into an embryonic stem cell-like state (1) but also into another, different, differentiated identity (2). Remarkably, this process, called direct cell-type conversion or transdifferentiation, also occurs naturally (2).…”
mentioning
confidence: 99%
“…For this proof-of-principle experiment, we decided to rescue a specific biological process: the Y-to-PDA transdifferentiation event, a model developed and characterized in the laboratory, where a single rectal epithelial cell called Y becomes a motorneuron called PDA during the L2 stage (Richard et al 2011;Hajduskova et al 2012;Zuryn et al 2012) We have shown that SEM-4 (a homolog of SALL) is crucial for the initiation of this reprogramming event as a member of a NODE-like complex (Jarriault et al 2008;. The sem-4(n1971) mutant, in which Y-to-PDA is 100% defective, can be rescued by expressing col-34p::sem-4a::HA::SL2::mCherry .…”
Section: A Peptides Can Simultaneously Deliver Five Distinct Functiomentioning
confidence: 99%
“… 78,79 Furthermore, various manipulations have been used to stimulate reprogramming of cells into a desired phenotype. 80 Notably, a few years ago it was demonstrated that depletion of GLD-1 and MEX-3, or GLD-1 alone, causes germ cells to ectopically transdifferentiate into various somatic cell types, forming human germ cell tumor-like teratomas. 67,81 However, epigenetic factors may confer resistance to efficient reprogramming to specific cell types.…”
Section: Alterations In Cell Death Pathways and Their Implications Inmentioning
confidence: 99%